Association of apolipoprotein E genotype with outcome in hospitalized ischemic stroke patients. Issue 50 (December 2017) - Zhang, Yajing; Liu, Shuling; Yue, Wei; Shi, Zhihong; Guan, Yalin; Li, Mingzi; Ji, Yong; Li, Xin
Abstract : Abstract: The aim of this study was to study the ability of the genotype to predict impairment and disability in hospitalized ischemic stroke (IS) patients after hospital discharge and 6 months after the onset of stroke symptoms. A total of 786 patients with a first IS were enrolled. Apolipoprotein E ( ApoE ) polymorphism was examined using polymerase chain reaction. Stroke subtype was classified using the Oxfordshire Community Stroke Project classification scheme and the Trial of Org 10172 in Acute Stroke Treatment criteria. Impairment as assessed using the National Institutes of Health Stroke Scale (NIHSS), and disability as measured using the modified Rankin Scale (mRS), were compared against the ApoE genotype. There was no significant association between the type of ApoE allele present and the stroke subtype. On multivariate regression analysis, the apolipoprotein E * E4 allele genotype did not predict poor outcome at discharge and or at 6 months after stroke onset. A higher NIHSS score on admission, older age, and higher fasting glucose levels did predict poor outcome at hospital discharge. Higher glucose levels and higher NIHSS scores on admission were independent risk factors predicting poor neurologic status at 6 months after stroke onset. The presence of the apolipoprotein E * E4 and apolipoprotein E * E2 genotypes, although related to cholesterol and triglyceride levels, do not affect recovery during rehabilitation. A higher NIHSS score on admission and a higher fasting glucose level predict poor neurologic status, both at hospital discharge and 6 months after onset.